Different radius of curvature at the talus trochlea from northern Chinese population measured using 3D model - Shixun Wu; Shizhang Liu; Minggang Huang; Zhe Liu; Jiyuan Shi; Ming Ling (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background To analyze the curvature characteristics of the talus trochlea in people from northern China in different sex and age groups. Methods Computed tomography scanning data of talus from 61 specimens were collected and constructed as a three-dimensional model by Materialise’s Interactive Medical Image Control System(MIMICS) software, anteromedial(AM), posteromedial(PM), anterolateral(AL), and posterolateral(PL) edge, anterior edge of medial trochlea, posterior edge of medial trochlea and anterior edge of lateral trochlea were defined according to the anatomical landmarks on trochlear surface. The curvature radii for different areas were measured using the fitting radius and measure module. Results There were significant differences among the talus curvatures in the six areas (F = 54.905, P = 0.000), and more trends in the analytical results were as follows: PM > PL > MP > AL > MA > AM. The average PL radius from specimens aged > 38 years old was larger than that from specimens aged < = 38 years (t=-2.303, P = 0.038). The talus curvature of the AM for males was significantly larger than that for females (t = 4.25, P = 0.000), and the curvature of the AL for males was larger than that for females (t = 2.629, P = 0.010). For observers aged < = 38 years, the AM curvature of the right talus in the male group was significantly larger than that in the female group (P < 0.01). In age < = 38years group, the MA curvature of right talus in male was significantly larger than in female group(P < 0.01), fitting radius of talus for male (21.90 ± 1.97 mm) was significantly greater than female of this(19.57 ± 1.26 mm)(t = 6.894, P = 000). The average radius of the talus in the male population was larger than that in the female population. Conclusion There was no significant relationship between age and talus curvature for males and females. The radius of curvature in the posterior area was significantly larger than that in the anterior area. We recommend that this characteristic of the talus trochlea should be considered when designing the talus component in total ankle replacement (TAR).